1998
DOI: 10.1002/hep.510280633
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis C in Children: A Clinical and Immunohistochemical Comparative Study With Adult Patients

Abstract: Limited information is available regarding the characteristics of the hepatitis C virus (HCV) infection in children.We compared the epidemiological background along with the virological and histological features as well as the intrahepatic immunologic phenotype of both children and adults with chronic hepatitis C (CHC). Serum samples of 24 pediatric and 32 adult patients were drawn for alanine transaminase (ALT) levels, HCV-typing, and viral load. The histological diagnosis and a semiquantitative immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 36 publications
4
46
0
Order By: Relevance
“…Studies conducted on children and adolescents have demonstrated a clinically benign course of HCV infection in this age group [13][14][15]. These studies reinforce the influence of age on the natural history of hepatitis C. On the other hand, studies conducted on older patients contaminated through blood transfusion have reported cirrhosis in about 50% of cases [3,16,17].…”
Section: Discussionmentioning
confidence: 59%
“…Studies conducted on children and adolescents have demonstrated a clinically benign course of HCV infection in this age group [13][14][15]. These studies reinforce the influence of age on the natural history of hepatitis C. On the other hand, studies conducted on older patients contaminated through blood transfusion have reported cirrhosis in about 50% of cases [3,16,17].…”
Section: Discussionmentioning
confidence: 59%
“…The course of HCV-associated chronic liver disease in children is usually milder than it is in adults, with lower levels of ALT, lower histological activity, and lower HCV levels, even without differences in HCV genotype distribution [18][19][20][21]. In keeping with observations in adult patients, the occurrence of NOSA has been described also in children [10,11].…”
Section: Discussionmentioning
confidence: 78%
“…According to current knowledge the inflammatory activity in liver tissue is usually mild at the time of diagnosis and may remain at a low level over more than 10 to 15 years. 6,7 The risk for developing cirrhosis probably will not exceed around 5% until adulthood. 8,9 Nevertheless, in single cases progressive liver diseases will occur and besides that the majority of infected individuals remain infectious.…”
mentioning
confidence: 99%